Determinants of Financial Distress with Institutional Ownership as a Moderating Variable in the Telecommunications Industry in Indonesia - Suhardian, Edward; Siswanti , Indra (International Journal Labs, 2025)
Indonesia's telecommunications sector serves as a key catalyst for economic growth and technological advancement in the era of globalization and Industry 4.0, with digital transformation acting as the primary force behind these changes. This study aims to analyze the influence of leverage, profitability, sales growth, and corporate social responsibility on financial distress. Furthermore, this research seeks to evaluate the role of institutional ownership as a moderating variable in affecting the relationship between these factors and financial distress. The method used in this study is Moderated Regression Analysis (MRA) with E-Views 12 software. The population in this study consists of 22 telecommunication companies listed on the Indonesia Stock Exchange during the 2019-2023 period and the sampling technique used is purposive sampling. The results show that leverage, profitability, sales growth has a significant negative effect on financial distress, while corporate social responsibility do not affect financial distress. Institutional ownership can moderate the influence of leverage and sales growth on financial distress but cannot moderate the effect of profitability and corporate social responsibility on financial distress.